Solid electrolytic capacitor and method of manufacturing same
By using a silver-containing layer in solid electrolytic capacitors composed of a mixture of large and small silver particles with an organic binder, the challenges of achieving high adhesion and low resistance are addressed, resulting in capacitors with low initial ESR and high heat resistance.
Patent Information
- Application Number
- JP2021029977
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-26
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-02-26
AI Technical Summary
Existing silver-containing layers in solid electrolytic capacitors face challenges in achieving high adhesion while maintaining low resistance, as the content of silver particles affects both adhesion and resistance.
A silver-containing layer is formed using a paste containing first silver-containing particles with a particle diameter over 1 μm and second silver-containing particles with a diameter under 50 nm, along with an organic binder, to achieve a silver content of 60% to 90% in the solid content, ensuring high adhesion and low resistance.
The proposed solution maintains a low initial equivalent series resistance (ESR) and ensures high heat resistance and reliability of the solid electrolytic capacitors.
Smart Images

Figure 0007664526000004 
Figure 0007664526000005 
Figure 0007664526000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a solid electrolytic capacitor and a method for manufacturing the same. [Background technology]
[0002] The solid electrolytic capacitor includes a solid electrolytic capacitor element, a resin exterior body or case that seals the solid electrolytic capacitor element, and an external electrode electrically connected to the solid electrolytic capacitor element. The solid electrolytic capacitor element includes an anode body, a dielectric layer formed on the surface of the anode body, and a cathode part that covers at least a part of the dielectric layer. The cathode part includes, for example, a solid electrolyte layer containing a conductive polymer that covers at least a part of the dielectric layer, and a cathode extraction layer that covers at least a part of the solid electrolyte layer. The cathode extraction layer includes, for example, a carbon layer that covers at least a part of the solid electrolyte layer, and a metal-containing layer that covers at least a part of the carbon layer. The cathode extraction layer is electrically connected to a cathode-side external electrode via a cathode lead.
[0003] For example, Patent Document 1 proposes a solid electrolytic capacitor in which a capacitor element is formed by successively forming a solid electrolyte layer, a carbon layer, and a conductor layer on a dielectric film formed on the surface of a sintered body obtained by molding and sintering valve action metal powder, and a cathode terminal is connected to the capacitor element via a conductive adhesive, the solid electrolytic capacitor being characterized in that a nano-conductor layer formed only from conductive nanoparticles is provided at at least one of the interfaces between the solid electrolyte layer and the carbon layer, the interface between the carbon layer and the conductor layer, and the interface between the conductor layer and the conductive adhesive.
[0004] In a solid electrolytic capacitor, for example, a metal-containing layer constituting a cathode extraction layer or a conductive adhesive layer connecting a cathode extraction layer and a cathode lead may be formed using a silver-containing paste containing silver particles. In addition, when a solid electrolytic capacitor includes a laminate of a plurality of solid electrolytic capacitor elements, a silver-containing paste may be used to fix adjacent solid electrolytic capacitor elements. In order to ensure high adhesion of the silver-containing layer, a silver-containing paste containing an organic binder in addition to silver particles may be used. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2009-252881 A Summary of the Invention [Problem to be solved by the invention]
[0006] The silver-containing layer formed using the silver-containing paste is required to have low resistance as well as high adhesion to the layer (or member such as a lead) that comes into contact with the silver-containing layer. From the viewpoint of ensuring high adhesion, it is advantageous to reduce the content of silver particles and increase the content of the organic binder. However, when the content of silver particles is low, the resistance of the silver-containing layer becomes high. When the content of silver particles is high, it is difficult to ensure sufficient adhesion of the silver-containing layer, and the silver-containing layer is prone to peeling. When the resistance of the silver-containing layer or the interlayer resistance between the silver-containing layer and the layer that comes into contact with the silver-containing layer becomes high, the equivalent series resistance (ESR) increases. [Means for solving the problem]
[0007] A first aspect of the present disclosure includes at least one solid electrolytic capacitor element including an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer, the cathode section includes a solid electrolyte layer covering at least a portion of the dielectric layer, and at least a portion of the cathode section includes a silver-containing layer including silver-containing particles and a resin phase, The silver-containing particles include first silver-containing particles having a particle diameter of more than 1 μm and second silver-containing particles having a particle diameter of 50 nm or less, The present invention relates to a solid electrolytic capacitor, wherein the silver content of the solid content of the silver-containing layer is 60 volume % or more and 90 volume % or less.
[0008] A second aspect of the present disclosure is a method for manufacturing a solid electrolytic capacitor including at least one solid electrolytic capacitor element including an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer, the method comprising: forming the cathode portion so as to cover at least a portion of the dielectric layer; the cathode section includes a solid electrolyte layer covering at least a portion of the dielectric layer, and at least a portion of the cathode section includes a silver-containing layer including silver-containing particles and a resin phase, the step of forming the cathode portion includes a step of forming the silver-containing layer by applying a silver-containing paste including first silver-containing particles having a particle diameter exceeding 1 μm, second silver-containing particles having a particle diameter of 50 nm or less, and an organic binder so as to cover at least a portion of at least one layer constituting the cathode portion; The present invention relates to a method for producing a solid electrolytic capacitor, wherein a volume ratio of silver to the total amount of silver and the organic binder in the silver-containing paste is 60 volume % or more and 90 volume % or less. Effect of the Invention
[0009] The initial ESR of the solid electrolytic capacitor can be kept low. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view of a solid electrolytic capacitor according to an embodiment of the present disclosure. [Diagram 2]FIG. 13 is a cross-sectional view that illustrates a capacitor element included in a solid electrolytic capacitor according to another embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] A silver-containing layer formed from a general silver-containing paste contains silver particles with a particle size on the order of micrometers and a resin phase. In such a silver-containing layer, the content of silver particles in the solid content is low at less than 60 volume %, and the inclusion of a large amount of resin phase provides relatively high adhesion. However, the resistance of the silver-containing layer tends to be high because of the high content of insulating resin phase and the low number of contact points between the silver particles. In addition, there are few contact points between the silver particles and layers in contact with the silver-containing layer, so the interfacial resistance between the layers is high. When the resistance of the silver-containing layer or the interfacial resistance between the layers increases, the ESR of the solid electrolytic capacitor increases.
[0012] In Patent Document 1, a nano-conductor layer using only conductive nanoparticles is formed at the interface between the carbon layer and the conductor layer. In such a nano-conductor layer, since there are many contact points between the nanoparticles, the conductivity may be high, but the adhesion is low. Due to the low adhesion of the nano-conductor layer, the nano-conductor layer may peel off from the carbon layer or cracks may form in the nano-conductor layer. In particular, when a solid electrolytic capacitor is exposed to high temperatures, stress due to expansion or the like is easily applied to the nano-conductor layer, so peeling or cracking is likely to occur. When peeling or cracking occurs, the resistance increases, and the ESR increases.
[0013] Depending on the application, solid electrolytic capacitors may be used in high-temperature environments. In addition, solid electrolytic capacitors are generally soldered to a substrate through a reflow process in which they are exposed to high temperatures. For this reason, solid electrolytic capacitors are required to have high heat resistance.
[0014] In the solid electrolytic capacitor of the present disclosure, the silver-containing layer constituting at least a part of the cathode part contains silver-containing particles and a resin phase. Here, the silver-containing particles include first silver-containing particles having a particle diameter of more than 1 μm and second silver-containing particles having a particle diameter of 50 nm or less. The silver content of the solid content of the silver-containing layer is 60 volume % or more and 90 volume % or less. Such a silver-containing layer may be referred to as a first silver-containing layer in this specification.
[0015] In the present disclosure, in the first silver-containing layer, in addition to the first silver-containing particles having a large particle diameter, small second silver-containing particles having a particle diameter of 50 nm or less are used, so that high adhesion can be ensured even if the silver content in the solid content is 60 volume % or more and 90 volume % or less, which is higher than the conventional one. In addition to the high silver content in the solid content of the first silver-containing layer, the first silver-containing particles have high bulk conductivity, and the second silver-containing particles increase the contact points between the second silver-containing particles and between the first silver-containing particles and the second silver-containing particles. As a result, the resistance of the first silver-containing layer can be kept low. By including the second silver-containing particles in the first silver-containing layer, many contact points between the second silver-containing particles and the layer in contact with the first silver-containing layer can be secured, so that the interlayer interface resistance can be kept low. Therefore, the initial ESR of the solid electrolytic capacitor can be kept low. Therefore, a solid electrolytic capacitor with excellent capacitor performance can be obtained.
[0016] In addition, in the solid electrolytic capacitor of the present disclosure, since the silver content is within the above range, the first silver-containing layer contains a certain amount of resin phase, so that the first silver-containing layer can have a moderate flexibility. Therefore, even if the solid electrolytic capacitor is exposed to high temperatures, stress due to expansion or the like can be alleviated, peeling of the first silver-containing layer and the occurrence of cracks in the first silver-containing layer can be suppressed, and an increase in ESR can be suppressed. In this way, the solid electrolytic capacitor of the present disclosure can also have high heat resistance. Therefore, the solid electrolytic capacitor has high reliability.
[0017] The first silver-containing layer can be formed using a silver-containing paste containing silver-containing particles and an organic binder. Here, the silver-containing particles include first silver-containing particles having a particle diameter of more than 1 μm and second silver-containing particles having a particle diameter of 50 nm or less. The volume ratio of silver to the total amount of silver and the organic binder in the silver-containing paste is 60 volume % or more and 90 volume % or less. Such a silver-containing paste for forming the first silver-containing layer may be referred to as the first silver-containing paste.
[0018] Hereinafter, the solid electrolytic capacitor and the manufacturing method thereof according to the present disclosure will be described in more detail with reference to the drawings as necessary.
[0019] [Solid electrolytic capacitor] A solid electrolytic capacitor includes one or more solid electrolytic capacitor elements. Hereinafter, the solid electrolytic capacitor elements may be simply referred to as capacitor elements.
[0020] (Capacitor element) (Anode body) The anode body included in the capacitor element may contain a valve metal, an alloy containing a valve metal, and a compound containing a valve metal. The anode body may contain one of these materials, or may contain two or more of them in combination. For example, aluminum, tantalum, niobium, and titanium are preferably used as the valve metal. The anode body having a porous surface is obtained by roughening the surface of a base material containing a valve metal (such as a sheet-shaped (e.g., foil-shaped, plate-shaped) base material) by etching or the like. The roughening can be performed by etching or the like. The anode body may also be a molded body of particles containing a valve metal or a sintered body thereof. Each of the molded body and the sintered body has a porous structure. Each of the molded body and the sintered body may be in a sheet shape, a rectangular parallelepiped, a cube, or a shape similar thereto.
[0021] The anode body usually has an anode lead and a cathode forming part. The cathode part is usually formed on the cathode forming part of the anode body via a dielectric layer. An anode lead is connected to the anode lead.
[0022] (Dielectric layer) The dielectric layer is an insulating layer that functions as a dielectric and is formed so as to cover at least a part of the surface of the anode body. The dielectric layer is formed by anodizing the valve metal on the surface of the anode body by chemical conversion treatment or the like. The dielectric layer may be formed so as to cover at least a part of the anode body. The dielectric layer is usually formed on the surface of the anode body. Since the dielectric layer is formed on the porous surface of the anode body, the surface of the dielectric layer has a fine uneven shape as described above.
[0023] The dielectric layer contains an oxide of the valve metal. For example, when tantalum is used as the valve metal, the dielectric layer contains Ta2O5, and when aluminum is used as the valve metal, the dielectric layer contains Al2O3. However, the dielectric layer is not limited to this, and it is sufficient if it functions as a dielectric.
[0024] (cathode) The cathode part is formed so as to cover at least a part of the dielectric layer formed on the surface of the anode body. Each layer constituting the cathode part can be formed by a known method according to the layer configuration of the cathode part.
[0025] The cathode section includes a solid electrolyte layer covering at least a portion of the dielectric layer. The cathode section may further include a cathode extraction layer covering at least a portion of the solid electrolyte layer. When the cathode extraction layer and the cathode lead are connected by a conductive adhesive, the cathode section herein also includes a conductive adhesive layer (hereinafter sometimes referred to as a first conductive adhesive layer) interposed between the cathode extraction layer and the cathode lead. In a solid electrolytic capacitor including a plurality of capacitor elements, when the plurality of capacitor elements are fixed by a conductive adhesive, the cathode section herein also includes a conductive adhesive layer (hereinafter sometimes referred to as a second conductive adhesive layer) fixing adjacent capacitor elements together (more specifically, the cathode section of one of the capacitor elements).
[0026] In the solid electrolytic capacitor of the present disclosure, the cathode part includes a first silver-containing layer in at least a part of the cathode part. The cathode part may include the first silver-containing layer in at least a part of at least one selected from the group consisting of a cathode extraction layer, a first conductive adhesive layer, and a second conductive adhesive layer. The cathode part may include a silver-containing layer other than the first silver-containing layer (hereinafter, may be referred to as a second silver-containing layer or a third silver-containing layer). For example, the cathode extraction layer may include a first layer containing conductive carbon and covering at least a part of the solid electrolyte layer, a second silver-containing layer as a second layer covering at least a part of the first layer, and the first silver-containing layer as a first conductive adhesive layer interposed between the second silver-containing layer and the cathode lead. The solid electrolytic capacitor may include a laminate in which a plurality of capacitor elements including a cathode extraction layer including the first layer and the second silver-containing layer as a second layer covering at least a part of the first layer are laminated via the first silver-containing layer as a second conductive adhesive layer. In such a laminate, the cathode extraction layer and the cathode lead of each capacitor element may be connected via the third silver-containing layer or the first silver-containing layer as the first conductive adhesive layer.
[0027] The components of the cathode section will now be described.
[0028] (solid electrolyte layer) The solid electrolyte layer is formed on the surface of the anode body via the dielectric layer so as to cover the dielectric layer. The solid electrolyte layer does not necessarily have to cover the entire dielectric layer (the entire surface), but may be formed so as to cover at least a part of the dielectric layer. The solid electrolyte layer constitutes at least a part of the cathode part in the solid electrolytic capacitor.
[0029] The solid electrolyte layer includes a conductive polymer. The conductive polymer includes, for example, a conjugated polymer and a dopant. The solid electrolyte layer may further include an additive, if necessary.
[0030] Conjugated polymers include known conjugated polymers used in solid electrolytic capacitors, such as π-conjugated polymers. Conjugated polymers include, for example, polymers having polypyrrole, polythiophene, polyaniline, polyfuran, polyacetylene, polyphenylene, polyphenylenevinylene, polyacene, and polythiophenevinylene as a basic skeleton. Of these, polymers having polypyrrole, polythiophene, or polyaniline as a basic skeleton are preferred. The above polymers may contain at least one type of monomer unit constituting the basic skeleton. The monomer unit also includes a monomer unit having a substituent. The above polymers also include homopolymers and copolymers of two or more types of monomers. For example, polythiophenes include poly(3,4-ethylenedioxythiophene) and the like.
[0031] The solid electrolyte layer may contain one type of conjugated polymer or a combination of two or more types of conjugated polymers.
[0032] The weight average molecular weight (Mw) of the conjugated polymer is not particularly limited, but is, for example, 1,000 or more and 1,000,000 or less.
[0033] In this specification, the weight average molecular weight (Mw) is a value calculated as polystyrene measured by gel permeation chromatography (GPC). GPC is usually measured using a polystyrene gel column and water / methanol (volume ratio 8 / 2) as the mobile phase.
[0034] The dopant may be, for example, at least one selected from the group consisting of anions and polyanions.
[0035] Examples of the anion include, but are not limited to, sulfate ion, nitrate ion, phosphate ion, borate ion, organic sulfonate ion, carboxylate ion, etc. Examples of the dopant that generates the sulfonate ion include benzenesulfonic acid, p-toluenesulfonic acid, and naphthalenesulfonic acid.
[0036] The polyanion may be a polymer anion, etc. The solid electrolyte layer may include, for example, a conjugated polymer including a monomer unit corresponding to a thiophene compound, and a polymer anion.
[0037] The polymer anion may be, for example, a polymer having a plurality of anionic groups. Such a polymer may include a polymer containing a monomer unit having an anionic group. Examples of the anionic group include a sulfonic acid group and a carboxy group.
[0038] In the solid electrolyte layer, the anionic group of the dopant may be contained in a free form, an anion form, or a salt form, or may be contained in a form bound to or interacting with a conjugated polymer. In this specification, all of these forms may be simply referred to as an "anionic group," "sulfonic acid group," "carboxy group," or the like.
[0039] Examples of polymer anions having a carboxy group include, but are not limited to, polyacrylic acid, polymethacrylic acid, and copolymers using at least one of acrylic acid and methacrylic acid.
[0040] Specific examples of polymer anions having a sulfonic acid group include, for example, polymer-type polysulfonic acids such as polyvinyl sulfonic acid, polystyrene sulfonic acid (including copolymers and substituted products having a substituent), polyallyl sulfonic acid, polyacrylic sulfonic acid, polymethacrylic sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, polyester sulfonic acid (such as aromatic polyester sulfonic acid), and phenolsulfonic acid novolac resin, but are not limited to these.
[0041] The amount of the dopant contained in the solid electrolyte layer is, for example, 10 to 1000 parts by mass, and may be 20 to 500 parts by mass, or 50 to 200 parts by mass, relative to 100 parts by mass of the conjugated polymer.
[0042] The solid electrolyte layer may further contain at least one selected from the group consisting of known additives and known conductive materials other than conductive polymers, as necessary. The conductive material may be at least one selected from the group consisting of conductive inorganic materials such as manganese dioxide and TCNQ complex salts. A layer for enhancing adhesion may be interposed between the dielectric layer and the solid electrolyte layer.
[0043] The solid electrolyte layer may be a single layer or may be composed of multiple layers. For example, the solid electrolyte layer may be composed to include a first solid electrolyte layer covering at least a part of the dielectric layer and a second solid electrolyte layer covering at least a part of the first solid electrolyte layer. The types, compositions, contents, etc. of the conjugated polymer, dopant, additive, etc. contained in each layer may be different or the same for each layer.
[0044] The solid electrolyte layer is formed, for example, by polymerizing a precursor on a dielectric layer using a treatment liquid containing a precursor of a conjugated polymer and a dopant. The polymerization can be performed by at least one of chemical polymerization and electrolytic polymerization. Examples of the precursor of the conjugated polymer include a monomer, an oligomer, and a prepolymer. The solid electrolyte layer may be formed by attaching a treatment liquid (for example, a dispersion liquid or a solution) containing a conductive polymer to a dielectric layer and then drying the applied liquid. Examples of the dispersion medium (or solvent) include at least one selected from the group consisting of water and an organic solvent. The treatment liquid may further include other components (such as at least one selected from the group consisting of a dopant and an additive).
[0045] When a treatment liquid containing a precursor of a conjugated polymer is used, an oxidizing agent is used to polymerize the precursor. The oxidizing agent may be contained in the treatment liquid as an additive. The oxidizing agent may be applied to the anode body on which the dielectric layer is formed before or after the treatment liquid is brought into contact with the anode body. Examples of such oxidizing agents include Fe 3+Examples of the oxidizing agent include compounds capable of generating oxidizing agent (such as ferric sulfate), persulfates (such as sodium persulfate and ammonium persulfate), and hydrogen peroxide. The oxidizing agent can be used alone or in combination of two or more kinds.
[0046] The process of forming a solid electrolyte layer by immersion in a treatment liquid and polymerization (or drying) may be carried out once or may be repeated several times. In each process, the conditions such as the composition and viscosity of the treatment liquid may be the same or at least one of the conditions may be changed.
[0047] (Cathode extraction layer) The cathode extraction layer must include at least a first layer that is in contact with the solid electrolyte layer and covers at least a portion of the solid electrolyte layer, and may include the first layer and a second layer that covers at least a portion of the first layer.
[0048] The first layer may be, for example, a layer containing conductive particles or a metal foil. The conductive particles may be, for example, at least one selected from conductive carbon and metal powder. For example, the cathode extraction layer may be composed of a layer containing conductive carbon (also referred to as a carbon layer) as the first layer and a layer containing metal powder or metal foil as the second layer. When metal foil is used as the first layer, the cathode extraction layer may be composed of this metal foil.
[0049] An example of the conductive carbon is graphite (artificial graphite, natural graphite, etc.).
[0050] The layer containing metal powder as the second layer can be formed, for example, by laminating a composition containing metal powder on the surface of the first layer. For example, the second layer can be a metal paste layer formed using a paste containing metal powder and a resin (binder resin). Although a thermoplastic resin can be used as the binder resin, it is preferable to use a thermosetting resin such as an imide resin or an epoxy resin. From the viewpoint of easily obtaining high conductivity of the second layer, silver-containing particles are preferable as the metal powder. Examples of the silver-containing particles include silver particles and silver alloy particles. The second layer may contain silver particles and silver alloy particles. From the viewpoint of ensuring higher conductivity of the second layer, silver particles are preferable as the silver-containing particles. The silver particles may contain a small amount of impurities. The second layer containing silver-containing particles may be a first silver-containing layer or a second silver-containing layer.
[0051] When a metal foil is used as the first layer, the type of metal is not particularly limited. For the metal foil, it is preferable to use a valve metal (aluminum, tantalum, niobium, etc.) or an alloy containing a valve metal. If necessary, the surface of the metal foil may be roughened. The surface of the metal foil may be provided with a chemical conversion film, or may be provided with a coating of a metal (heterogeneous metal) different from the metal constituting the metal foil or a nonmetal. Examples of the heterogeneous metal or nonmetal include metals such as titanium and nonmetals such as carbon (conductive carbon, etc.).
[0052] The coating of the dissimilar metal or non-metal (eg, conductive carbon) may be the first layer, and the metal foil may be the second layer.
[0053] When the cathode extraction layer includes the first silver-containing layer, the entire cathode extraction layer may be composed of the first silver-containing layer, the first layer may be composed of the first silver-containing layer, or the second layer may be composed of the first silver-containing layer. For example, the cathode extraction layer may include a first layer containing conductive carbon and a second layer including the first silver-containing layer covering at least a part of the first layer.
[0054] The cathode extraction layer is formed by a known method depending on its layer structure. For example, when the cathode extraction layer includes a metal foil as the first layer or the second layer, the first layer or the second layer is formed by laminating the metal foil so as to cover at least a part of the solid electrolyte layer or the first layer. The first layer including conductive particles is formed, for example, by applying a conductive paste or liquid dispersion including conductive particles and, if necessary, a resin binder (such as a water-soluble resin or a curable resin) to the surface of the solid electrolyte layer. The second layer including metal powder is formed, for example, by applying a paste including metal powder and a resin binder to the surface of the first layer. In the process of forming the cathode extraction layer, a drying process, a heating process, or the like may be performed as necessary.
[0055] (First conductive adhesive layer) The solid electrolytic capacitor includes a cathode lead. In the solid electrolytic capacitor, the cathode lead is connected to a cathode extraction layer via a first conductive adhesive layer. When the solid electrolytic capacitor includes a plurality of capacitor elements, the cathode extraction layer and the cathode lead of some of the capacitor elements may be connected via the first conductive adhesive layer. The first conductive adhesive layer electrically connects the cathode extraction layer and the cathode lead of the capacitor element.
[0056] The first conductive adhesive layer may be formed using a known conductive adhesive. Examples of known conductive adhesives include pastes containing conductive particles and a resin binder (such as a curable resin). The first conductive adhesive layer formed using a known conductive adhesive may be a second silver-containing layer formed using a known silver-containing adhesive (such as a silver-containing paste). Such a first conductive adhesive layer is formed, for example, by arranging the above-mentioned paste (including the silver-containing paste) so as to be sandwiched between the cathode extraction layer and the cathode lead. For example, the above-mentioned paste may be applied or transferred to a part of the surface of the cathode extraction layer, and a part of one end side of the cathode lead may be overlapped on the coating of the paste formed. In the process of forming the first conductive adhesive layer, a drying process, a heating process, or the like may be performed as necessary.
[0057] The first conductive adhesive layer may be a first silver-containing layer. In this case, the cathode part includes the first silver-containing layer interposed between the cathode extraction layer and the cathode lead.
[0058] (Second conductive adhesive layer) When the solid electrolytic capacitor includes a plurality of capacitor elements, the plurality of capacitor elements may be fixed via a second conductive adhesive layer. For example, when the solid electrolytic capacitor includes a laminate of a plurality of capacitor elements, the plurality of capacitor elements may be laminated via a second conductive adhesive layer. The second conductive adhesive layer may be in contact with the cathode lead layer of each capacitor element. The second conductive adhesive layer electrically connects the plurality of capacitor elements.
[0059] The second conductive adhesive layer may be formed using a known conductive adhesive. Examples of known conductive adhesives include pastes containing conductive particles and a resin binder (such as a curable resin). The second conductive adhesive layer formed using a known conductive adhesive may be a third silver-containing layer formed using a known silver-containing adhesive (such as a silver-containing paste). Such a second conductive adhesive layer is formed, for example, by arranging the above-mentioned paste (including the silver-containing paste) so as to be sandwiched between adjacent capacitor elements. For example, the above-mentioned paste may be applied or transferred to a part of the surface of the cathode extraction layer of the capacitor element, and another capacitor element may be placed on the coating of the paste formed. In the process of forming the second conductive adhesive layer, drying treatment, heating treatment, etc. may be performed as necessary.
[0060] The second conductive adhesive layer may be the first silver-containing layer, in which case adjacent solid electrolytic capacitor elements are fixed via the first silver-containing layer.
[0061] The first silver-containing layer included in the cathode part will be described in more detail below.
[0062] (Silver containing layer) The first silver-containing layer contains silver-containing particles. The silver-containing particles include at least first silver-containing particles having a particle diameter of more than 1 μm and second silver-containing particles having a particle diameter of 50 nm or less. If necessary, the silver-containing particles may further include third silver-containing particles having a particle diameter of more than 50 nm and 1 μm or less.
[0063] By including the first silver-containing particles and the second silver-containing particles having the above particle diameter in the first silver-containing layer, the second silver-containing particles enter between the first silver-containing particles, enhancing the effect of shortening the distance between the silver-containing particles. In addition, the number of contact points between the silver-containing particles increases, so that the resistance in the first silver-containing layer can be further reduced.
[0064] The first silver-containing layer is formed using a first silver-containing paste containing silver-containing particles and an organic binder. The silver-containing particles include at least first and second silver-containing particles, and may include third silver-containing particles as necessary. When the first silver-containing paste contains second silver-containing particles having a particle diameter of 50 nm or less, the second silver-containing particles having a small particle diameter can be fused to adjacent silver-containing particles at a relatively low temperature when a heat treatment is performed in the manufacturing process of the solid electrolytic capacitor. Therefore, in the first silver-containing layer formed, the conductive path can be expanded, and the conductivity can be further increased. Therefore, in the first silver-containing layer, the silver-containing particles may include particles (sometimes referred to as aggregated particles) in which silver-containing particles having a primary particle diameter of 50 nm or less are fused to adjacent silver-containing particles. The aggregated particles are sometimes called secondary particles. Such aggregated particles are formed, for example, by at least a part of the second silver-containing particles contained in the first silver-containing paste being fused to adjacent silver-containing particles (for example, at least one of the first silver-containing particles and the second silver-containing particles). The aggregated particles may be formed by at least a part of the second silver-containing particles contained in the first silver-containing paste fusing with the third silver-containing particles. In the first silver-containing layer, the aggregated particles may be any of the first silver-containing particles, the second silver-containing particles, and the third silver-containing particles depending on the particle diameter.
[0065] In the first silver-containing layer, the particle diameter of each silver-containing particle is the maximum diameter of the silver-containing particle obtained from the cross-sectional image of the first silver-containing layer. For example, when the shape of the silver-containing particle observed in the cross-sectional image is elliptical, the long axis of the ellipse is the maximum diameter. In the cross-sectional image, the silver-containing particle can have any shape. The particle diameter of the above-mentioned aggregated particle is the maximum diameter of the aggregated particle obtained from the cross-sectional image of the first silver-containing layer. In the cross-sectional image, voids may be formed inside the silver-containing particle. Depending on the particle diameter (i.e., the maximum diameter) of the silver-containing particle obtained from the cross-sectional image, the silver-containing particle (including the above-mentioned aggregated particle) is classified into the first silver-containing particle, the second silver-containing particle, and the third silver-containing particle.
[0066] The particle diameter of the silver-containing particles is measured, for example, by using a cross-sectional image of a portion of a capacitor element including the first silver-containing layer taken with a scanning electron microscope (SEM). A sample for photographing can be prepared, for example, by the following procedure. First, a solid electrolytic capacitor is embedded in a curable resin, and the curable resin is cured. The cured product is wet-polished or dry-polished to expose a cross section parallel to the thickness direction of the cathode part (a cross section where the stacking state of each layer of the cathode part can be confirmed). The exposed cross section is smoothed by ion milling to obtain a sample for photographing.
[0067] The first silver-containing layer is identified from the particle size and content of the silver-containing particles in a cross-sectional image taken by SEM.
[0068] The silver-containing particles include silver particles, silver alloy particles, etc. The first silver-containing layer may contain silver particles and silver alloy particles. From the viewpoint of ensuring higher electrical conductivity of the first silver-containing layer, silver particles are preferred as the silver-containing particles. The silver particles may contain a small amount of impurities.
[0069] The silver content in the solid content of the first silver-containing layer is 60% by volume or more, and may be 65% by volume or more. When the silver content is in such a range, it is advantageous in ensuring higher electrical conductivity of the first silver-containing layer. The silver content is preferably 90% by volume or less, and may be 85% by volume or less. When the silver content is in such a range, the content of the resin phase can be relatively increased, so that higher adhesion of the first silver-containing layer can be ensured. From the viewpoint of ensuring higher heat resistance and reliability, the silver content is preferably 74% by volume or less or 70% by volume or less. These lower limit values and upper limit values can be arbitrarily combined. The silver content in the solid content of the first silver-containing layer is the volume ratio (volume %) of silver when the entire solid content excluding voids (including voids contained in the silver-containing particles) contained in the first silver-containing layer is 100% by volume.
[0070] Examples of the resin constituting the resin phase contained in the first silver-containing layer include thermoplastic resins and curable resins (or compositions thereof). From the viewpoint of ensuring higher adhesion, curable resins (such as thermosetting resins and photocurable resins) or compositions thereof are preferred. The curable resins or compositions thereof may be cured in the first silver-containing layer. From the viewpoint of easily ensuring high adhesion and high heat resistance, among the curable resins, epoxy resins, polyamideimide resins, polyimide resins, phenolic resins, and the like are preferred. The resin phase of the first silver-containing layer may contain one type of resin or a combination of two or more types of resins.
[0071] The content of the resin phase in the first silver-containing layer is, for example, 9.5% by volume or more, preferably 14% by volume or more, and more preferably 15% by volume or more. By making the content of the resin phase in such a range, the first silver-containing layer can be ensured to have high adhesion and high flexibility, and the occurrence of cracks in the first silver-containing layer and peeling of the first silver-containing layer can be suppressed. From the viewpoint of ensuring higher heat resistance and reliability, the content of the resin phase in the first silver-containing layer is preferably 26% by volume or more. The content of the resin phase in the first silver-containing layer is, for example, 40% by volume or less, preferably 38% by volume or less, and may be 35% by volume or less. When the content of the resin phase is in such a range, the resistance of the first silver-containing layer can be suppressed low. These lower and upper limits can be combined arbitrarily.
[0072] The first silver-containing layer may contain voids. The voids are formed, for example, by volatilization of a volatile component such as a liquid medium or an additive during the formation of the first silver-containing layer. When the first silver-containing layer contains voids, the flexibility of the first silver-containing layer is increased, which is advantageous in reducing the occurrence of cracks. The porosity of the first silver-containing layer is, for example, 5% by volume or less.
[0073] The silver content, resin phase content, and porosity in the solid content of the first silver-containing layer are obtained from a cross-sectional image of the capacitor element including the first silver-containing layer by SEM. More specifically, in the cross-sectional image by SEM, element mapping is performed by energy dispersive X-ray spectroscopy (EDX) for a predetermined region (e.g., a region of 5 μm×5 μm) of the first silver-containing layer, and the area ratio of each region is obtained by distinguishing the regions of silver, resin phase, and voids. The ratio (area%) of the area of voids to the entire area of the predetermined region is defined as the porosity, and the ratio (area%) of silver and resin phase to the total area of silver and resin phase is defined as the silver content (area%) and the resin component content (area%) in the solid content. Similar analysis is performed for multiple fields of view (e.g., 5 fields of view) and averaging is performed. The obtained average values are the porosity (volume %) in the first silver-containing layer, the silver content (volume %) in the solid content of the first silver-containing layer, and the resin content (volume %). The cross-sectional image by SEM is obtained in the same manner as in the case of measuring the particle size. The magnification of the cross-sectional image by SEM is 1000 times or more and 50000 times or less.
[0074] In a 5 μm×5 μm region R of the cross section of the first silver-containing layer, the ratio (=S1 / S2) of the area S1 occupied by the first silver-containing particles having a particle diameter larger than 1 μm to the area S2 occupied by the other silver-containing particles (second silver-containing particles and third silver-containing particles) is, for example, 10 / 90 to 90 / 10, or may be 20 / 80 to 90 / 10, 40 / 60 to 90 / 10, or 20 / 80 to 85 / 15. In the region R, it is preferable that at least five second silver-containing particles can be confirmed in the part corresponding to the area S2. In such a case, the resistance of the first silver-containing layer can be kept low, and better adhesion can be ensured. The sum of the areas S1 and S2 is calculated in accordance with the case of the silver content in the solid content of the first silver-containing layer described above. The area S1 is calculated by image analysis from the cross section obtained by the SEM described above. The area S1 is an average value obtained for multiple visual fields (for example, five visual fields). The area S2 is obtained by subtracting the area S1 from the sum of the area S1 and the area S2.
[0075] The thickness of the first silver-containing layer is, for example, 0.5 μm to 100 μm, and may be 1 μm to 50 μm. From the viewpoint of ensuring higher adhesion of the first silver-containing layer and easily maintaining low resistance, the thickness of the first silver-containing layer may be 1 μm to 20 μm.
[0076] The thickness of the first silver-containing layer is determined by measuring the thickness of the first silver-containing layer at multiple points (for example, 10 points) in the cross-sectional image taken by the SEM described above and averaging the thicknesses.
[0077] The first silver-containing layer can be formed by applying the first silver-containing paste so as to cover at least a part of at least one layer constituting the cathode part. Therefore, in the method for producing a solid electrolytic capacitor, the step of forming the cathode part includes a step of forming such a first silver-containing layer. The at least one layer constituting the cathode part includes a layer in contact with the first silver-containing layer in the cathode part, such as a solid electrolyte layer, a cathode extraction layer, a first or second layer constituting the cathode extraction layer, and a cathode lead. The coating of the first silver-containing paste applied so as to cover at least a part of the at least one layer constituting the cathode part may be subjected to at least one of a drying treatment and a heating treatment, if necessary.
[0078] The first silver-containing paste contains silver-containing particles and an organic binder, and may contain a liquid medium as needed. The liquid medium may be a liquid medium at a temperature at which the first silver-containing paste is applied, and may be a liquid medium at room temperature (for example, 20°C to 35°C). For example, an organic solvent is used as the liquid medium. An organic solvent and water may be used in combination as the liquid medium. The first silver-containing paste may contain other additives as needed. When the first silver-containing paste contains a liquid medium, the liquid medium contained in the coating film can be removed by carrying out the above-mentioned drying treatment.
[0079] The silver-containing particles include first and second silver-containing particles. The silver-containing particles may include third silver-containing particles. For these silver-containing particles, the description of the first silver-containing particles, the second silver-containing particles, and the third silver-containing particles described in the first silver-containing layer can be referred to.
[0080] The volume ratio of silver to the total amount of silver and the organic binder in the first silver-containing paste can be selected, for example, from the range described for the silver content in the solid content of the first silver-containing layer.
[0081] The volume ratio of the first silver-containing particles to the second silver-containing particles in the first silver-containing paste (=first silver-containing particles / second silver-containing particles) is, for example, 10 / 90 to 90 / 10, or may be 20 / 80 to 90 / 10, 40 / 60 to 90 / 10, 20 / 80 to 85 / 15, or 20 / 80 to 83 / 17. When the volume ratio is in such a range, a first silver-containing layer having low resistance and higher adhesion can be formed.
[0082] The particle size of each silver-containing particle in the first silver-containing paste is determined from the volumetric particle size distribution of the silver-containing particles separated from the first silver-containing paste. The volumetric particle size distribution of the silver-containing particles is measured using a particle size distribution measuring device using dynamic light scattering. As the particle size distribution measuring device using dynamic light scattering, for example, a light scattering photometer DLS-8000 manufactured by Otsuka Electronics Co., Ltd. is used.
[0083] In addition, a dispersion liquid containing silver-containing particles separated from the first silver-containing paste is used to measure the volumetric particle size distribution of the silver-containing particles contained in the first silver-containing paste. The dispersion liquid is prepared, for example, by the following procedure. First, a predetermined amount of the first silver-containing paste is collected and diluted by adding an organic solvent that dissolves the organic binder. The diluted product is separated into a solid (sample A) and a liquid (liquid I) by centrifuging. The solid sample A is washed with an organic solvent that dissolves the organic binder and dried to obtain silver-containing particles (sample B). At this time, the liquid (liquid II) obtained by washing with the organic solvent is collected separately. The sample B is dispersed in a liquid dispersion medium using a dispersant to prepare a dispersion liquid for particle size distribution measurement. For example, an organic medium that is liquid at room temperature (for example, 20°C to 35°C) is used as the dispersion medium. The type and concentration of the dispersant, the type of the dispersion medium, and the concentration of the sample B in the dispersion liquid may be selected within a range in which a dispersion liquid suitable for measuring the particle size distribution can be prepared.
[0084] The volume ratio of the first silver-containing particles to the second silver-containing particles is determined from the particle size distribution measured by the dynamic light scattering method. The sum of the volume ratio of the first silver-containing particles and the volume ratio of the second silver-containing particles is calculated from the volume of both silver-containing particles contained in a predetermined amount of the first silver-containing paste determined from the particle size distribution measured by the dynamic light scattering method and the volume of the organic binder contained in a predetermined amount of the first silver-containing paste. The liquid I and liquid II are mixed and concentrated, and the liquid medium is removed, and the volume of the resulting residue corresponds to the volume of the organic binder.
[0085] The organic binder contained in the first silver-containing paste may be a thermoplastic resin, a curable resin, or a composition thereof, as described above with respect to the resin constituting the resin phase of the first silver-containing layer. The organic binder contained in the first silver-containing paste may contain a curable resin, and may further contain additives (such as a curing agent, a curing accelerator, or a catalyst) that may constitute a composition of the curable resin. When the first silver-containing paste contains a thermosetting resin or a composition thereof, the thermosetting resin can be cured by carrying out the above-mentioned heating step. The heating temperature may be determined according to the composition of the organic binder.
[0086] The formed first silver-containing layer may be heated at a temperature of 150°C or more and 260°C or less, if necessary. Since the first silver-containing paste contains the second silver-containing particles having a small particle size, when the heat treatment is performed at such a temperature, the second silver-containing particles can be fused with the adjacent silver-containing particles. Therefore, the resistance of the first silver-containing layer can be further reduced. The heating temperature may be 150°C or more and 230°C or less. Such a heat treatment can be performed at an appropriate stage after the first silver-containing layer is formed. For example, the heat treatment may be performed after the first silver-containing layer is formed and before sealing with a resin outer casing or case, or after sealing. When the organic binder contains a thermosetting resin or a composition thereof, the thermosetting resin or the composition thereof may be cured by such a heat treatment. The heat treatment time may be, for example, 10 seconds or more and 2 hours or less, and may be 1 minute or more and 1 hour or less.
[0087] (others) The solid electrolytic capacitor may be of a wound type, and may be either a chip type or a laminate type. For example, the solid electrolytic capacitor may include a laminate of two or more capacitor elements. When the solid electrolytic capacitor includes a plurality of capacitor elements, each capacitor element may be, for example, of a wound type or a laminate type. The configuration of the capacitor element may be selected according to the type of the solid electrolytic capacitor.
[0088] When a metal foil is used for the cathode extraction layer, a separator may be disposed between the metal foil and the anode body. The separator is not particularly limited, and may be, for example, a nonwoven fabric containing fibers of cellulose, polyethylene terephthalate, vinylon, or polyamide (e.g., aliphatic polyamide, aromatic polyamide such as aramid).
[0089] In the capacitor element, one end of the cathode lead is electrically connected to the cathode extraction layer. One end of the anode lead is electrically connected to the anode body. The other end of the anode lead and the other end of the cathode lead are each drawn out from the resin exterior body or the case. The other end of each lead exposed from the resin exterior body or the case is used for solder connection with a substrate on which the solid electrolytic capacitor is to be mounted, or the like. Each lead may be a lead wire or a lead frame.
[0090] The capacitor element is sealed with a resin exterior body or case. For example, the capacitor element and the resin material of the exterior body (e.g., uncured thermosetting resin and filler) may be placed in a mold, and the capacitor element may be sealed with the resin exterior body by transfer molding, compression molding, or the like. At this time, the other end side of the anode lead and the other end side of the cathode lead drawn out from the capacitor element are exposed from the mold. Alternatively, the capacitor element may be placed in a bottomed case such that the other end side of the anode lead and the other end side of the cathode lead are positioned on the opening side of the bottomed case, and the opening of the bottomed case may be sealed with a sealer to form a solid electrolytic capacitor.
[0091] Fig. 1 is a cross-sectional view that shows a schematic structure of a solid electrolytic capacitor according to an embodiment of the present disclosure. As shown in Fig. 1, the solid electrolytic capacitor 1 includes a capacitor element 2, a resin outer casing 3 that seals the capacitor element 2, and an anode lead 4 and a cathode lead 5, at least a portion of which is exposed to the outside of the resin outer casing 3. The anode lead 4 and the cathode lead 5 can be made of a metal such as copper or a copper alloy. The resin outer casing 3 has an outer shape of a substantially rectangular parallelepiped, and the solid electrolytic capacitor 1 also has an outer shape of a substantially rectangular parallelepiped.
[0092] The capacitor element 2 includes an anode body 6, a dielectric layer 7 covering the anode body 6, and a cathode portion 8 covering the dielectric layer 7. The cathode portion 8 includes a solid electrolyte layer 9 covering the dielectric layer 7, a cathode extraction layer 10 covering the solid electrolyte layer 9, and a first conductive adhesive layer 14A formed of a conductive adhesive. The cathode extraction layer 10 and the cathode lead 5 are electrically connected via the first conductive adhesive layer 14A. The cathode extraction layer 10 includes a first layer 11 covering the solid electrolyte layer 9, and a second layer 12 covering the first layer. For example, at least one of the second layer 12 and the first conductive adhesive layer 14A may be formed of the first silver-containing layer.
[0093] The anode body 6 includes a region facing the cathode portion 8 and a region not facing the cathode portion 8. Of the region of the anode body 6 not facing the cathode portion 8, an insulating separation portion 13 is formed in a strip-like shape covering the surface of the anode body 6 in a portion adjacent to the cathode portion 8, thereby restricting contact between the cathode portion 8 and the anode body 6. Of the region of the anode body 6 not facing the cathode portion 8, another part is electrically connected to the anode lead 4 by welding.
[0094] Fig. 2 is a cross-sectional view showing a schematic diagram of a capacitor element included in a solid electrolytic capacitor according to another embodiment. In Fig. 2, three capacitor elements 102A, 102B, and 102C are laminated with a second conductive adhesive layer 14B interposed therebetween. For convenience, Fig. 2 shows only the laminated body of these capacitor elements, and omits the dielectric layer. Fig. 2 differs from Fig. 1 in that three capacitor elements are laminated and a second conductive adhesive layer 14B is provided, but the description of Fig. 1 can be referred to for other configurations.
[0095] In FIG. 2, each of the capacitor elements 102A, 102B, and 102C includes an anode body 6, a dielectric layer covering the anode body 6, and a cathode section 108 covering the dielectric layer, as in the case of FIG. 1. The cathode section 108 includes a solid electrolyte layer 9 covering the dielectric layer, and a cathode lead layer 10 covering the solid electrolyte layer 9. The adjacent capacitor elements 102A and 102B are fixed to each other via a second conductive adhesive layer 14B formed of a conductive adhesive. Similarly, the capacitor elements 102B and 102C are fixed to each other via a second conductive adhesive layer 14B. The second conductive adhesive layer 14B is also included in the cathode section 108. In the cathode section 108, at least one of the cathode lead layer 10 and the second conductive adhesive layer 14B may be formed of the first silver-containing layer. In the laminate of the capacitor elements 102A, 102B, and 102C, a cathode lead may be connected to some of the capacitor elements. A first conductive adhesive layer is formed between the cathode lead and the cathode extraction layer 10 of the capacitor element to which the cathode lead is connected. Such a first conductive adhesive layer may be formed of the above-mentioned first silver-containing layer.
[0096] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0097] Examples 1 to 3 and Comparative Examples 1 to 2 A capacitor element was produced in the following manner, and its characteristics were evaluated.
[0098] (1) Preparation of the anode An anode body was prepared by roughening both surfaces of an aluminum foil (thickness: 100 μm) used as a substrate by etching.
[0099] (2) Formation of the dielectric layer The other end of the anode body was immersed in a chemical conversion solution, and a direct current voltage of 10 V was applied for 20 minutes to form a dielectric layer containing aluminum oxide.
[0100] (3) Formation of solid electrolyte layer An aqueous solution containing a pyrrole monomer and p-toluenesulfonic acid was prepared, the monomer concentration in the aqueous solution being 0.5 mol / L and the p-toluenesulfonic acid concentration being 0.3 mol / L.
[0101] The anode body on which the dielectric layer was formed in (2) above and a counter electrode were immersed in the obtained aqueous solution, and electrolytic polymerization was performed at 25°C and a polymerization voltage of 3 V (polymerization potential relative to the silver reference electrode) to form a solid electrolyte layer.
[0102] (4) Formation of the cathode The anode body obtained in (3) above was immersed in a dispersion liquid in which graphite particles were dispersed in water, and then removed from the dispersion liquid and dried to form a first layer (carbon layer) at least on the surface of the solid electrolyte layer. The drying was performed at 150° C. for 30 minutes.
[0103] Next, a silver-containing paste containing at least one of the first silver-containing particles and the second silver-containing particles and an epoxy resin as an organic binder was applied to the surface of the first layer, and the paste was heated at 210°C for 10 minutes to form a second layer, which was a silver-containing layer. The epoxy resin was converted into a hardened material by heating. In this way, a cathode extraction layer composed of the first layer and the second layer was formed. Silver particles were used as the first silver-containing particles and the second silver-containing particles. The thickness of the second layer was about 10 μm.
[0104] The silver-containing paste was prepared by mixing silver-containing particles, an organic binder and a liquid medium (or a dispersion or solution containing an organic binder) as necessary. At this time, the amount of each component was adjusted when preparing the silver-containing paste so that the volume ratio (volume %) of silver to the total amount of silver and the organic binder in the silver-containing paste and the volume ratio of the first silver-containing particles and the second silver-containing particles, both of which were obtained by the procedure already described for the first silver-containing paste, were the values shown in Table 1. Note that, as the silver-containing paste containing only the second silver-containing particles as silver particles, a silver-containing paste containing the second silver-containing particles, a volatile dispersant and a volatile liquid medium was used.
[0105] A capacitor element was produced in the manner described above. A total of 20 capacitor elements were produced in the same manner. The obtained capacitor elements were used for the evaluation described below.
[0106] In the obtained Example, when the cross section of the second layer (first silver-containing layer) was observed by SEM imaging, aggregated particles in which silver-containing particles having a primary particle size of 50 nm or less were fused to the surrounding silver-containing particles were confirmed. Also, when the cross section of the second layer of the capacitor element of Comparative Example 2 was observed by SEM imaging, silver-containing particles having a primary particle size of 50 nm or less were fused to the surrounding silver-containing particles throughout the entire second layer.
[0107] (5) Assembly of solid electrolytic capacitors The cathode extraction layer of the capacitor element obtained in (4) above is bonded to one end of the cathode lead using a conductive adhesive. Also, one end of the anode body that is not covered by the solid electrolyte layer and the cathode extraction layer is bonded to one end of the anode lead by laser welding. Then, a resin outer casing made of insulating resin is formed around the capacitor element by molding. At this time, the other end of the anode lead and the other end of the cathode lead are pulled out from the resin outer casing. The solid electrolytic capacitor is assembled in this manner.
[0108] Examples 4 to 6 and Comparative Examples 3 to 4 Two capacitor elements were prepared in the same manner as in Comparative Example 1. A silver-containing paste was applied to the surface of the cathode lead layer of one of the capacitor elements, and the two capacitor elements were stacked so that the cathode lead layer of the other capacitor element was in contact with the coating of the silver-containing paste. In this state, the two capacitor elements were heated at 210°C for 10 minutes to form a second conductive adhesive layer interposed between the cathode lead layers. In this manner, a total of 20 laminates of capacitor elements were prepared. The resulting laminates were used for the evaluation described below.
[0109] The silver-containing paste was prepared by mixing silver-containing particles, an organic binder and a liquid medium (or a dispersion or solution containing an organic binder) as necessary. At this time, the amount of each component was adjusted when preparing the silver-containing paste so that the volume ratio (volume %) of silver to the total amount of silver and binder in the silver-containing paste and the volume ratio of the first silver-containing particles and the second silver-containing particles, both of which were obtained by the procedure already described for the first silver-containing paste, were the values shown in Table 2. Note that as the silver-containing paste containing only the second silver-containing particles as silver particles, a silver-containing paste containing the second silver-containing particles, a volatile dispersant and a volatile liquid medium was used.
[0110] Examples 7 to 9 and Comparative Examples 5 to 6 A total of 20 capacitor element laminates were produced in the same manner as in Examples 4 to 6 and Comparative Examples 3 to 4. A silver-containing paste was applied to the exposed surface of the cathode extraction layer of the capacitor element in each laminate, and the lead frame was placed on top of the laminate and heated at 210°C for 10 minutes. In this manner, a first conductive adhesive layer was formed between the cathode extraction layer and the lead frame. The capacitor element laminates thus obtained, to which the lead frame was bonded, were used for the evaluation described below. As the silver-containing paste, the silver-containing paste used for forming the second conductive adhesive layer in Examples 4 to 6 and Comparative Examples 3 to 4, respectively, was used.
[0111] Examples 10 to 12 and Comparative Example 7 In the second layer of the cathode extraction layer, the amount of each component was adjusted when preparing the silver-containing paste so that the volume ratio (volume %) of silver to the total amount of silver and organic binder in the silver-containing paste and the volume ratio of the first silver-containing particles and the second silver-containing particles, both of which were obtained by the procedure already described for the first silver-containing paste, were values shown in Table 3. A total of 20 capacitor elements were produced in the same manner as in Example 1, except that the second layer having the thickness shown in Table 3 was formed using such a silver-containing paste. The obtained capacitor elements were used for the evaluation described below.
[0112] [evaluation] The capacitor elements or the laminates of the capacitor elements were used to carry out the following evaluations.
[0113] (a) Initial ESR For Examples 1 to 9 and Comparative Examples 1 to 6, the initial ESR (mΩ) of each capacitor element or laminate of capacitor elements was measured at a frequency of 100 kHz using a four-terminal LCR meter in an environment of 20°C. The average initial ESR was calculated for 20 capacitor elements or laminates of capacitor elements. The initial ESRs of Examples 1 to 3 and Comparative Example 2 were expressed as a ratio when the initial ESR of Comparative Example 1 was set to 100%. The initial ESRs of Examples 4 to 6 and Comparative Example 4 were expressed as a ratio when the initial ESR of Comparative Example 3 was set to 100%. The initial ESRs of Examples 7 to 9 and Comparative Example 6 were expressed as a ratio when the initial ESR of Comparative Example 5 was set to 100%.
[0114] (b) ESR after accelerated testing For Examples 10 to 12 and Comparative Example 7, an accelerated test was performed by leaving the capacitor elements in a 145°C environment for 500 hours without load. The ESR after the accelerated test was measured in a 20°C environment using the same procedure as in the case of the initial ESR in (a) above, and the median ESR of the 20 capacitor elements was calculated. The ESR in the accelerated test for each capacitor element was expressed as a ratio when the median ESR of Comparative Example 7 was set to 100%.
[0115] The evaluation results are shown in Tables 1 to 3. E1 to E12 are Examples 1 to 12, and C1 to C7 are Comparative Examples 1 to 7. In the capacitor elements of the examples, the porosity of the first silver-containing layer determined by the procedure described above was 5 volume % or less. In the capacitor element of Comparative Example 1, almost no voids were found in the second layer. In the capacitor element of Comparative Example 2, the porosity of the second layer determined by the same procedure as in the case of the first silver-containing layer was about 40%.
[0116] [Table 1]
[0117] As shown in Table 1, when the second layer of the cathode lead layer was formed using only the second silver-containing particles as the silver-containing particles, the initial ESR increased by 30% compared to when only the first silver-containing particles were used as the silver-containing particles, even though the content of silver-containing particles in the second layer was high (comparison between C1 and C2). In C2, the second silver-containing particles were in a state of being fused to the surrounding second silver-containing particles throughout the second layer, so it is considered that the second layer had a relatively high conductivity. Nevertheless, the initial ESR of C2 was 30% higher than that of C1, which is considered to be due to the fact that the absence of a resin phase reduced the adhesion between the first and second layers, causing peeling.
[0118] From the results of C1 and C2, it is not expected that the ESR will decrease even when the second layer contains both the first silver-containing particles and the second silver-containing particles. However, when the first silver-containing particles and the second silver-containing particles are actually used in combination in the second layer, the initial ESR can be kept low (E1 to E3). This is thought to be because the resin phase improves the adhesion between the first layer and the second layer, suppressing an increase in the interfacial resistance between the layers due to peeling between the first layer and the second layer, and also because the second layer has high conductivity due to the high bulk conductivity of the first silver-containing particles and the increase in the contact points between the silver-containing particles.
[0119] [Table 2]
[0120] As shown in Table 2, the effect of reducing the initial ESR can be obtained even if the first conductive adhesive layer or the second conductive adhesive layer is used as the first silver-containing layer.
[0121] [Table 3]
[0122] As shown in Table 3, in the example, the increase in ESR is suppressed even after an accelerated test at 145° C. for 500 hours. Thus, in the example, high heat resistance is obtained and excellent reliability can be ensured. [Industrial Applicability]
[0123] The solid electrolytic capacitor of the present disclosure has a low initial ESR and excellent capacitor performance. In addition, the solid electrolytic capacitor has high heat resistance and high reliability. Therefore, the solid electrolytic capacitor can be used for various applications. [Explanation of symbols]
[0124] 1: solid electrolytic capacitor, 2, 102A, 102B, 102C: capacitor element, 3: resin outer casing, 4: anode lead, 5: cathode lead, 6: anode body, 7: dielectric layer, 8, 108: cathode portion, 9: solid electrolyte layer, 10: cathode lead layer, 11: first layer, 12: second layer, 13: separator, 14A: first conductive adhesive layer, 14B: second conductive adhesive layer
Claims
1. at least one solid electrolytic capacitor element including an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer; the cathode section includes a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode extraction layer covering at least a portion of the solid electrolyte layer, the cathode extraction layer includes a first layer that contains conductive carbon and covers at least a portion of the solid electrolyte layer, and a second layer that covers at least a portion of the first layer, the cathode part includes, in at least a portion of the cathode part, a silver-containing layer including silver-containing particles and a resin phase, The silver-containing particles include first silver-containing particles having a particle diameter of more than 1 μm and second silver-containing particles having a particle diameter of 50 nm or less, A solid electrolytic capacitor, wherein the silver content of the silver-containing layer is 65 volume % or more and 90 volume % or less in the solid content.
2. 2. The solid electrolytic capacitor according to claim 1, wherein the silver-containing layer has a silver content of 85 volume % or less in the solid content.
3. The solid electrolytic capacitor according to claim 1 , wherein the silver-containing layer contains voids.
4. 4. The solid electrolytic capacitor according to claim 1, wherein the silver-containing particles include aggregate particles in which adjacent silver-containing particles are fused together, the aggregate particles having a primary particle size of 50 nm or less.
5. A solid electrolytic capacitor described in any one of claims 1 to 4, wherein the second layer includes a silver-containing layer covering at least a portion of the first layer.
6. Further comprising a cathode lead; 6. The solid electrolytic capacitor according to claim 1, further comprising the silver-containing layer interposed between the cathode extraction layer and the cathode lead.
7. A plurality of the solid electrolytic capacitor elements are included, 7. The solid electrolytic capacitor according to claim 1, wherein adjacent solid electrolytic capacitor elements are fixed via the silver-containing layer.
8. 8. The solid electrolytic capacitor according to claim 1, wherein the silver-containing layer has a thickness of 1 μm or more and 20 μm or less.
9. A method for manufacturing a solid electrolytic capacitor including at least one solid electrolytic capacitor element including an anode body, a dielectric layer formed on a surface of the anode body, and a cathode portion covering at least a portion of the dielectric layer, comprising: forming the cathode portion so as to cover at least a portion of the dielectric layer; the cathode section includes a solid electrolyte layer covering at least a portion of the dielectric layer, and a cathode extraction layer covering at least a portion of the solid electrolyte layer, the cathode extraction layer includes a first layer that contains conductive carbon and covers at least a portion of the solid electrolyte layer, and a second layer that covers at least a portion of the first layer, the cathode part includes, in at least a portion of the cathode part, a silver-containing layer including silver-containing particles and a resin phase, the step of forming the cathode part includes a step of forming the silver-containing layer by applying a silver-containing paste including first silver-containing particles having a particle diameter exceeding 1 μm, second silver-containing particles having a particle diameter of 50 nm or less, and an organic binder so as to cover at least a part of at least one layer constituting the cathode part; a volume ratio of silver to the total amount of silver and the organic binder in the silver-containing paste is 65 volume % or more and 90 volume % or less.
10. 10. The method for producing a solid electrolytic capacitor according to claim 9, wherein the step of forming the silver-containing layer includes a step of heating a coating of the silver-containing paste formed so as to cover at least a portion of the at least one layer constituting the cathode portion at a temperature of 150° C. or more and 260° C. or less.
Citation Information
Patent Citations
Solid-state electrolytic capacitor
JP2003173937A
Solid electrolytic capacitor and its manufacturing method
JP2004165423A
Solid electrolytic capacitor and manufacturing method thereof
JP2005093741A
Solid electrolytic capacitor and manufacturing method thereof
JP2006253169A
Conductive paste for solid electrolytic capacitor electrode, and manufacturing method of electrode of solid electrolytic capacitor using the conductive paste
JP2008300637A